2016
DOI: 10.1890/15-1759.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating local biodiversity change: a critique of papers claiming no net loss of local diversity

Abstract: Global species extinction rates are orders of magnitude above the background rate documented in the fossil record. However, recent data syntheses have found mixed evidence for patterns of net species loss at local spatial scales. For example, two recent data meta-analyses have found that species richness is decreasing in some locations and is increasing in others. When these trends are combined, these papers argued there has been no net change in species richness, and suggested this pattern is globally represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
292
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(303 citation statements)
references
References 59 publications
8
292
2
1
Order By: Relevance
“…However, our recovery metric ‘diversity' includes other diversity measurements that account for differences in abundance, which could be responsible for this contrast. Nonetheless, our results agree with the worst scenarios estimated for the effects of land-use change on local species richness of plants and animals11, and with the reanalysis of references1415, showing that spatial and temporal biases in these meta-analysis do not support a no net change of α-diversity16. This highlights that species assemblages could be more resilient to anthropogenic disturbance than populations, even when most individuals are lost.…”
Section: Discussionsupporting
confidence: 86%
“…However, our recovery metric ‘diversity' includes other diversity measurements that account for differences in abundance, which could be responsible for this contrast. Nonetheless, our results agree with the worst scenarios estimated for the effects of land-use change on local species richness of plants and animals11, and with the reanalysis of references1415, showing that spatial and temporal biases in these meta-analysis do not support a no net change of α-diversity16. This highlights that species assemblages could be more resilient to anthropogenic disturbance than populations, even when most individuals are lost.…”
Section: Discussionsupporting
confidence: 86%
“…In many ecosystems, environmental change causes biodiversity declines or increases [2629]. Experiments that directly and randomly manipulate biodiversity are unlikely to predict function in these ecosystems (Fig.…”
Section: The Re-introduction Of Environmental Change Drivers Is Needementioning
confidence: 99%
“…Second, working with a large amount of data requires careful consideration of the possible biases, statistical issues and inferences that can be drawn when using these data. For example, one recent study 32 identified multidimensional biases, gaps and uncertainties in global plant occurrence information data in the GBIF database, while another work 33 examined spatial biases in collected data sets used in two different meta-analysis that (wrongly) concluded that there was no net loss of biodiversity due to anthropogenic disturbances. This does not warn against data reuse, but rather calls for a rigorous scientific approach that identifies and accordingly addresses potential issues.…”
Section: Data Misinterpretation and Potential Biasesmentioning
confidence: 99%